Quantification and Characterization of Trichoderma Spp. from Different Habitats - Choo, Chee Wei (2003)
The abundance of Trichoderma was not significantly different between the oil palm cultivated areas and jungle areas. Soil pH and soil moisture content did not have an effect on the abundance of Trichoderma in the areas sampled. Ganoderma infected area with percentage disease incidence (PDI) of> 30% recorded higher frerquency (9.5 x 103 cfu/g air dried soil) of isolation of Trichoderma. In the reserved forest habitat, inland soil seemed to harbor higher population (10.9 x 103 cfu/g dried soil) of Trichoderma. Generally for all habitats and areas sampled, the two upper soil horizons (AI and Be) supported higher population of Trichoderma and the distribution decreased with depth of soil. However, in the EFB mulched area there was a significant increase in Trichoderma with increase in depth of profile. Based on phenotype appearances, four species aggregates of Trichoderma were identified from oil palm and forest rhizospheres, namely T. harzianum, T virens, T koningii, and T. longibrachiatum. T. harzianum and r virens were the most frequently isolated species aggregates while T longibrachiatum was the least. The variation between species aggregates of Trichoderma was distinguished by using RAPD. However, overlapping was found between T. virens and T. koningii and T. longibrachiatum within a main cluster. Isolates of the same species were group together within the same sub cluster indicating a close genetic linkage among the same species. Several putative DNA markers were identified that could be used for interspecies differentiation if consecutive PCR tests were carried out with primer OPC-II and OPC-I5. Confrontation assay based on percentage inhibition of mycelial growth and c010ny overgrowth showed that there were variations in the degree of antagonistic ability between and within species aggregates of Trichoderma. The mode of action was attributed to competition, mycoparasitism and / or antibiosis. Isolates TH80 of T. harzianum, TK126 of T. koningii and TV26 of T. virens were found to be the most effective antagonists.